Innovation and Development of Nursing Innovation - wongchanhan, kamonroj; Ruetrakul, Jirarat (NU Journal of Nursing and Health Sciences, 2025)
This article presents the development of innovation and the innovation development process in nursing. Nursing innovation is a crucial factor in developing the healthcare system and improving the quality of patient care to be more effective. The process of developing nursing innovation consists of several steps, starting from identifying healthcare problems or needs, creating innovative ideas or models, experimenting and refining, to implementing and evaluating the innovation in practice. The success of the innovation depends on the involvement of nursing personnel, organizational support, and the appropriate use of technology.In the modern era, nursing innovation plays a significant role in contemporary nursing, whether by improving patient outcomes or enhancing the efficiency of nursing practice. Nursing innovations include artificial intelligence systems for patient data analysis, health-tracking applications, robotic technology for patient care, and evidence-based nursing approaches. Promoting and developing nursing innovations is essential to ensuring optimal healthcare efficiency and adapting to the evolving healthcare system in the future.